2000
DOI: 10.1038/sj.leu.2401975
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative status of primitive hematopoietic progenitors from patients with acute myelogenous leukemia (AML)

Abstract: One possible explanation for the competitive advantage that malignant cells in patients with acute myelogenous leukemia (AML) appear to have over normal hematopoietic elements is that leukemic progenitors proliferate more rapidly than their normal progenitor cell counterparts. To test this hypothesis, an overnight

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 31 publications
2
35
0
Order By: Relevance
“…Accordingly, loss of p53 might contribute to the formation of leukemia-initiating cells, which by definition have maintained or reacquired the capacity for indefinite selfrenewal through accumulated mutations and/or epigenetic changes (Passegue and Weisman 2005). Such cells have properties reminiscent of cancer stem cells, which are considered to be inherently more aggressive and refractory to chemotherapy (Guan and Hogge 2000;Jordan and Guzman 2004;Holtz et al 2005). Consequently, our results suggest a biological explanation for the occurrence of p53 mutations in the most aggressive and drugresistant AMLs.…”
Section: Prevention Of Aberrant Self-renewal and Tumor Suppression Bymentioning
confidence: 75%
“…Accordingly, loss of p53 might contribute to the formation of leukemia-initiating cells, which by definition have maintained or reacquired the capacity for indefinite selfrenewal through accumulated mutations and/or epigenetic changes (Passegue and Weisman 2005). Such cells have properties reminiscent of cancer stem cells, which are considered to be inherently more aggressive and refractory to chemotherapy (Guan and Hogge 2000;Jordan and Guzman 2004;Holtz et al 2005). Consequently, our results suggest a biological explanation for the occurrence of p53 mutations in the most aggressive and drugresistant AMLs.…”
Section: Prevention Of Aberrant Self-renewal and Tumor Suppression Bymentioning
confidence: 75%
“…Normal stem cells cycle less frequently than the more differentiated transit-amplifying cells (thus, the designation of normal stem cells as label retaining). CSCs from acute and chronic myelogenous leukemias are relatively quiescent 58,59 , contributing to therapeutic resistance. Similar results have not been confirmed in CSCs derived from solid tumors.…”
Section: Cscs and Chemotherapy Resistancementioning
confidence: 99%
“…[15][16][17] Hatfield et al 18 reported the production of IL-3 from microvascular endothelium of bone marrow resulting in the proliferation and inhibition of apoptosis of AML blasts. Bone marrow stromal cells also produce IL-6 and stem cell factor (SCF).…”
Section: Introductionmentioning
confidence: 99%